Upaya Peningkatan Manajemen Akademik Sekolah - Rizky Kesuma Rahman (Jurnal Soshum Insentif, 2019)
The focus of the problem in this study examines the effectiveness of academic management systems in vocational schools in the city of Bandung. In this case, the effectiveness of the academic management system can be determined by the information system used by schools (hardware, software, databases, networks and HR) and. This study aims to determine and analyze the description of the information system, and the effectiveness of the school's academic management system, as well as measuring the magnitude of the effect of the Information System and on the Effectiveness of the Academic Management System of Schools in Vocational Schools in the City of Bandung. This research was conducted using a quantitative approach with survey methods. This research design is grouped into descriptive and verification research to analyze the causality relationship between the variables studied. The sample in this study was 77 CBK in the City of Appeal. Primary data sources were obtained from the distribution of questionnaires to 385 respondents (principals, teachers, and laboratory assistants). The results of the descriptive analysis show that overall Information Systems (Hardware, Software, Databases, Networks, and Human Resources) in Vocational Schools in the City of Bandung are included in the category of adequate. Included in the category have been well implemented, while the school's academic management system cannot be said to be effective. Information systems positively and significantly affect. Information Systems and positively and significantly affect the Effectiveness of the School Academic Management System. Overall, the school should have a computer-based academic information system application that can integratedly manage the school's academic administration orderly, supported by adequate infrastructure or computer infrastructure in accordance with their respective functions (hardware, software, databases, networks). Good planning and the creation of realistic implementation stages will be more successful and the benefits will be felt rather than plans that are too high but difficult to implement both because of the lack of funding and resources, especially human resources. All of this continues to be evaluated in order to improve the effectiveness of the school's academic management system.